Consistent stall air speeds in commercial dairy farms are associated with less variability in cow lying times - Reuscher, Kimberly J.; Cook, Nigel B.; Halbach, Courtney E.; Mondaca, Mario R.; Van Os, Jennifer M. C. (Frontiers in Animal Science, 2024)
Heat stress is a known challenge for dairy farms, but standardized, practical heat abatement assessments are lacking. Our objectives were to evaluate the summer ventilation system performance of Wisconsin freestall facilities, provide farms with feedback, and refine our assessment method for knowledge transfer to the industry. Six naturally ventilated (NV) and 6 cross-ventilated (CV) facilities (n=12) were enrolled. On d 1, 30 focal cows received data loggers to measure resting behavior and intravaginal temperature. Data loggers recorded barn air temperature and relative humidity. Air speeds (AS) were measured manually with anemometers to characterize AS distributions at cow resting (0.5m) and standing (1.5m) heights. Data loggers were removed on d 5, resulting in 3 d of data for resting behavior, vaginal temperature, and Temperature Humidity Index (THI). The fixed effects of average AS and daily maximum THI on daily maximum vaginal temperature (VT), 24-h lying time (LT), and the number and duration of daily lying bouts were analyzed using linear mixed models. We evaluated the fixed effects of THI, average AS, and within-facility SD in AS among stalls on within-facility SD of VT, LT, and number and duration of lying bouts among focal cows. Stall AS in NV vs. CV barns was 1.4±0.3 vs. 2.0±0.7 m/s (inter-facility ranges: 0.9–1.7 vs. 1.4–3.1 m/s) at resting height and 2.3±0.3 vs. 2.5±0.5 m/s (range: 1.7–2.8 vs. 1.7–3.1 m/s) at standing height. When facility AS increased by 1 m/s, cows had 0.8 fewer lying bouts per day. When the within-facility SD of AS among stalls increased by 1 m/s, the SD among cows of daily lying time increased 1 h/d, driven by an increase in the SDs of lying bouts (+2.5 bouts/d) and durations (13.9 min/bout). For every 10-unit increase in THI, VT increased 0.4°C, daily lying bouts tended to increase by 0.9/d, and SD of daily lying time increased 0.4 h/d. Farms received reports with summary data and suggestions to improve the consistency of AS at cow resting height. Consistent air speeds of ≥1 m/s among stalls can improve cow comfort during heat stress by reducing variation in lying behavior.